Establishing nursing-sensitive quality indicators for the operating room: A cross-sectional Delphi survey conducted in China. Issue 1 (January 2017) - Wu, Qi; Huang, Li-Hua; Xing, Mei-Yuan; Feng, Zhi-Xian; Shao, Le-Wen; Zhang, Mei-Yun; Shao, Rong-Ya
Abstract: Background: Nursing-sensitive quality indicators comprise principles, procedures, and assessments to quantify the level of nursing quality in hospital departments. Although studies have demonstrated that quality indicators are essential for monitoring nursing practice in the operating room (OR), nursing quality in China is highly subjective and localised OR nursing-sensitive quality indicators are lacking. Objective: This study aimed to establish scientific, objective and comprehensive nursing-sensitive quality indicators for the OR to evaluate and monitor OR nursing care quality in China. Methods: Literature search for relevant evidence-based studies was performed using Cochrane, Medline, PubMed, Embase, and other databases, followed by literature review and group discussion by the expert panel. Two successive rounds of Delphi surveys were conducted using questionnaires completed by the expert panel to reach consensus and define nursing-sensitive quality indicators for the OR. Results: Two rounds of Delphi surveys each had 100% questionnaire retrieval rate, with Kendall W coordination coefficients ranging from 0.096 to 0.263 ( P < 0.001). In round 1 of expert evaluation of 26 indicators, Kendall's W was 0.263 for importance, 0.126 for rationality, and 0.125 for feasibility of data collection (all P < 0.001). After round 2, 23 items were established as OR nursing-sensitive quality indicators, including rates of work time wastage, surgery start-time delay, OR turnover time between surgeries, same-day surgery cancellation, and number of monthly surgeries in each OR; checking surgical patients, surgery site marking, allergy history, and antibiotics use 60 min before incision; and also assessing expected surgical time, sterilisation indicator results, availability of surgical instruments and materials, and instrument count. Conclusions: Scientific, practical, and reliable OR nursing-sensitive quality indicators can be established based on evidence-based studies and expert consensus using the Delphi method. The quality indicators developed in this study may provide an objective and quantitative reference for evaluating nursing quality in Chinese ORs.